2014
DOI: 10.1556/amicr.61.2014.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the possible aetiological role of different Candida species in pathogenesis of dentine caries by monitoring the calcium release from tooth particles

Abstract: An in vitro model has been developed for study of cariogenic potential of different Candida species. Slices were prepared from the root of extracted healthy teeth. These disks were covered with inert material, only the central hole, i.e. the root canal dentin surface remained uncovered. These preparates with free root dentin surfaces were incubated in Sabouraud medium in the presence of six-six Candida albicans, Candida glabrata, Candida tropicalis, Candida krusei, Candida inconspicua and Candida norvegensis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…To evaluate the acidogenicity of the 35 clinical isolates of Candida species, in terms of degrading the mineralized components of the tooth structure, a calcium-release assay was performed, according to Nikawa et al [31] and Szabo et al [32], with some modifications. Acidogenicity was concomitantly evaluated by pH measurements of the incubating media.…”
Section: Evaluation Of Biofilm Formationmentioning
confidence: 99%
“…To evaluate the acidogenicity of the 35 clinical isolates of Candida species, in terms of degrading the mineralized components of the tooth structure, a calcium-release assay was performed, according to Nikawa et al [31] and Szabo et al [32], with some modifications. Acidogenicity was concomitantly evaluated by pH measurements of the incubating media.…”
Section: Evaluation Of Biofilm Formationmentioning
confidence: 99%
“…Nikawa, et al 22 (2003) demonstrated that the capacity of C. albicans to dissolve hydroxyapatite is nearly 20 times greater than S. mutans . Recently, Szabó, et al 29 (2014) demonstrated that Candida spp. are able to dissolve dentine and release calcium to the medium at different rates.…”
Section: Discussionmentioning
confidence: 99%
“…The biofilm matrix of C. albicans is mainly composed by β 1,3-glucan that builds up its structure, provides antifungal resistance and also provides sites for GtfB activity in dual species biofilms with S. mutans 9 . Therefore, the greater quantity of polysaccharides observed in C. albicans biofilms from sickle-cell anemia patients characterizes the formation of a denser and thicker biofilm 5 , 6 , which would enhance the adherence of microorganisms and would have a greater resistance to antimicrobial drugs penetration 3 , 7 , 9 , 29 . However, the impact of the higher amount of extracellular polysaccharides on biofilm thickness and on antimicrobial resistance should be assessed further.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations